Influence of Specimen Velocity on the Leakage Signal in Magnetic Flux Leakage Type Nondestructive Testing - Fawzi Belblidia (Journal of Nondestructive Evaluation, 2015)
We investigate the influence of the specimen velocity on the magnetic flux leakage with the aim of selecting the optimum sensor locations. Parametric numerical simulations where the specimen velocity was in the range [0.1–20] m/s were carried out. As the specimen velocity is increased, the magnetic field varies from being symmetrical to being asymmetric. For the radial magnetic induction B_z , the position at which the maximum difference between the minimum and maximum signal moves from the centre of the bridge towards the direction of the specimen movement. For the axial magnetic induction B_y , the specimen velocity influence is dependent on the sensor location and a signal-velocity independent region was discussed.